1998
DOI: 10.1038/bjc.1998.197
|View full text |Cite
|
Sign up to set email alerts
|

Schistosomiasis and the risk of bladder cancer in Alexandria, Egypt

Abstract: Summary The relationship between history of schistosomiasis and bladder cancer risk was investigated using data from a case-control study conducted between January 1994 and July 1996 in Alexandria, Egypt. Cases were 190 subjects with incident, histologically confirmed invasive cancer of the bladder, and controls were 187 subjects admitted to hospital for acute, non-neoplastic, non-urinary tract conditions. Eighty-six cases (45%) vs 69 controls (37%) reported a history of urinary schistosomiasis. The correspond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
64
0
7

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(74 citation statements)
references
References 13 publications
3
64
0
7
Order By: Relevance
“…2,3 Genetic factors such as polymorphisms in the detoxifying enzymes N-acetyltransferase 2 and glutathione S-transferase mu 1 may modify the risk of bladder cancer associated with environmental exposures. 4,5 Some infections, including Schistosoma hematobium 6 and frequent urinary tract infections, 7 have been associated with bladder cancer, although findings for the latter association are not consistent across studies. 2,8 It is unclear whether infections may induce chronic inflammation, 9 predisposing the bladder urothelium to malignant transformation by exogenous carcinogens, or whether the infectious agents themselves may be involved in the initiation or promotion of bladder cancer.…”
mentioning
confidence: 99%
“…2,3 Genetic factors such as polymorphisms in the detoxifying enzymes N-acetyltransferase 2 and glutathione S-transferase mu 1 may modify the risk of bladder cancer associated with environmental exposures. 4,5 Some infections, including Schistosoma hematobium 6 and frequent urinary tract infections, 7 have been associated with bladder cancer, although findings for the latter association are not consistent across studies. 2,8 It is unclear whether infections may induce chronic inflammation, 9 predisposing the bladder urothelium to malignant transformation by exogenous carcinogens, or whether the infectious agents themselves may be involved in the initiation or promotion of bladder cancer.…”
mentioning
confidence: 99%
“…Bladder cancer is one of the cancers that are closely associated with infection-induced inflammation. Schistosomiasis is a well-established risk factor in northern Africa (8). In the United States, a large epidemiologic study of 2,982 bladder cancer patients and 5,782 population controls showed that a history of urinary tract infection significantly increased the risk of bladder cancer, especially in individuals who had three or more infections (9).…”
mentioning
confidence: 99%
“…Research thus far suggests that infections with the parasite are particularly common in men in developing countries, such as Turkey and Egypt [26,27].…”
Section: Environmental Factorsmentioning
confidence: 99%